ANALISIS KETERSEDIAAN DAN KEBUTUHAN AIR DI DAERAH ALIRAN SUNGAI RORAYA PROVINSI SULAWESI TENGGARA - La Baco S.; Kahirun Kahirun; Umar Ode Hasani; Abdul Jalil (Universitas Haluoleo, 2017)
The recent phenomenon associated with the existence of water resources is a decrease in water supply while water demand continues to increase over time which is a logical consequence of population growth and increased economic activity. The purpose of this study was to analyze the availability and demand of water in the Roraya watershed. The research method used is the collection and analysis of secondary data. The results showed that water supply in the Roraya watershed was 3.75 m3/sec or 324,000 m3/day. The total water demand is 326,897 m3/day which is the cumulative value of domestic water demand of 16,316 m3/day, the demand of non domestic water is 3,263 m3/day, the need of irrigation water is 283,738 m3/day and the industrial water demand is 23,580 m3/day. Most of the water demand in the Roraya watershed is irrigation water of 86.6% of the total water demand in the Roraya watershed, while the domestic water demand in the Roraya watershed is about 5.0%. Industrial water demand in the Roraya watershed reached 7.2%, while non-domestic water demand only reached 1% of the total water demand in the Roraya watershed. The balance of water supply and demand in the Roraya watershed shows that every day there will be a water deficit of 2,897 m3/day. Key Words: Water Supply, Water Demand